Comparison of the removal efficiency of acid orange and acid black dyes using synthesized graphene oxide nanoparticles - Hossien Rezaei (مجله علمی دانشگاه علوم پزشکی کردستان, 2020)
Background and Aim: Colored wastewater discharged from industries can contaminate surface and groundwater. The aim of this study was to evaluate the efficiency of synthetic graphene oxide (GO) in the removal of industrial dyes. Materials and Methods: Graphene oxide was synthesized by use of the hydrothermal method and its physical and chemical properties were investigated. The parameters studied were initial dye concentration, pH, adsorbent dose, and contact time. Results: TEM and SEM analysis of adsorbents showed that GO was formed separately and with a nanostructured layer. The results revealed that efficiency decreased by increasing the concentration of pollutants and increased by increasing the adsorbent dose. The highest efficiency (>0.92%) was obtained at acidic pH after 120 minutes. The results also showed that the adsorption process follows the Langmuir isotherm model (R2> 0.99), and the reaction kinetic fitted with pseudo-second-order kinetic. Conclusion: The use of GO for the removal of dyes in aqueous solutions was an applicable and suitable method. We recommend this method for the removal of dye pollutants which are dangerous for the environment and human life.